Tax competition and governmental efficiency: Theory and evidence - Maksym Ivanyna (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2008)
This paper studies the impact of a government's efficiency on the taxation policy of a state. Namely, we claim that the countries are different both in the way they tax capital and the way they spend the collected revenue. We build a model of 2 countries competing for foreign investment, government of one of them is more efficient than the other one, which means that it is able to produce more public good out of the same revenue. We show that the country with the more efficient government will charge higher income tax from firms. The theoretical predictions are then tested on a sample of OECD countries, years 1996-2005. In general, empirical results are in line with the theory.
Keywords: F23; H25; H32; H54; H71; H73; 330; international taxation; public finance; asymmetric equilibrium; tax competition